EVALUATION OF DRUG PRESCRIBED IN PREGNANT WOMEN AND ITS COMPARISON WITH THE CATEGORIES OF THE FOOD AND DRUG ADMINISTRATION (FDA) IN KABUL, AFGHANISTAN 2021: A DESCRIPTIVE, CROSS-SECTIONAL STUDY - Murtaza Jafari; Zohal Shamriz; Tahmina Shamriz; Palwasha Rahmani; Mohammad Basir Sajadi (Journals Park Publishing, 2022)
Pregnancy is one of the natural periods in women's lives, during which the body undergoes physiological changes. These changes also affect the effects of the drug. Taking the drug during pregnancy requires caution, and the life of the fetus and mother is endangered by taking it arbitrarily and without consulting a doctor.
Keywords: Pregnancy; physiological changes; fetus